Design of Drainage Dimensions on the Ismail Harun Road, Percut Sei Tuan District - Nofriadi; Muflih Arif Maulana (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Roads are the most widely used transportation infrastructure by the people of Indonesia to carry out daily activities, with the increasing flow of vehicles passing a road segment, it must be balanced by good pavement conditions. To achieve this balance, we need a design that is in accordance with the events in the field. In addition, to meet the good character of the road, it must be equipped with water channels or drainage. Because the drainage channel or water channel is one of the complementary buildings that must be on the road to drain water so that the road body remains dry. Drainage channel is one of the technical requirements of road infrastructure. The alarming condition can be seen on Jalan Ismail Harun, Percut Sei Tuan District, Deli Serdang Regency. One of the access roads connecting Deli Serdang and Medan City was badly damaged. The road was flooded with water so that the road surface condition was not visible. To overcome this, this research is needed in the form of a design / design of drainage dimensions on the road segment. The method used in designing the drainage dimensions is the Road Drainage Planning Guidelines Method Pd T-02-2006-B. The results of the drainage dimension design are the cross-sectional width (b) of 0.7 m, the cross-sectional height (h) of 0.35 m and the guard height (w) of 0.4 m.